The sternum reconstruction: Present and future perspectives - Beatrice Aramini; Valentina Masciale; Lorenzo Federico Zini Radaelli; Rossella Sgarzani; Massimo Dominici; Massimo Dominici; Franco Stella (Frontiers in Oncology, 2022)
Sternectomy is a procedure mainly used for removing tumor masses infiltrating the sternum or treating infections. Moreover, the removal of the sternum involves the additional challenge of performing a functional reconstruction. Fortunately, various approaches have been proposed for improving the operation and outcome of reconstruction, including allograft transplantation, using novel materials, and developing innovative surgical approaches, which promise to enhance the quality of life for the patient. This review will highlight the surgical approaches to sternum reconstruction and the new perspectives in the current literature.